Book Review: A Practitioner’s Reflections in Response to ‘Human Rights Law and the Marginalized Other’ - Gimbad, Petra (Kathmandu School of Law Review, 2013)
This book review will have little theoretical grounds on political philosophy. Therefore, given my ability to critique Simmons’ interpretations of various philosophers is limited, I write this review from the perspective of a human rights practitioner seeking a reader to understand how contemporary philosophy may be used to interpret the practices of human rights in contemporary world . This review will focus on the questions that were raised in the course of reading the book. With reference to thinkers in particular, I hav e chosen to mention a little more on Hanna Arendt and Spivak, whom I tried to acquaint myself with, when I had the time in the past. I fully admit that much of my analysis may lack and hope that readers will not be prevented from discovering these philosophers on their own terms.